Effect of adipose tissue processing procedures in culture result: a study preliminary (Faculty of Medicine Universitas Indonesia, 2011)
Background: There are various methods of processing adipose tissue before culture, depending on the adipose tissue samples. The aim of this study is to compare several modifications of culturing and sub-culturing procedures of adipose tissue to fit the condition in our laboratory. Method: This is a descriptive study that was done in the Immunology and Endocrinology Integrated Laboratory, University of Indonesia, from October 2009 to April 2010. Three adipose tissue processing procedures, various amount of seeding and two subculture methods were compared in term of cell yield and time needed. In the first procedure, collagenase-1 digestion was done in 30minutes, cell seeding were 24,000 and 36,000 per flask; in the second procedure, collagenase-1 digestion was done in 60minutes, cell seeding were 24,000, 48,000, and 72,000 per flask; and in the third procedure, the adipose tissue remnants from the first procedure were again digested for another 45 minutes, cell seeding were 74,000, and 148,000 per flask. Difference in subculture methods were the presence or absence of washing step. Result: Procedure 1 yielded the lowest amount of cell, and after culture, the cells grew very slow, and was contaminated before harvest of primary culture. Procedure-2 and -3 succeeded to yield primary cultures. Some of the cultures were contaminated, so that further subculture was not applicable, and only one tissue processing procedure (procedure 2: 60 minute collagenase-1 digestion, without lysis buffer, cell seeding 48,000 and 72,000) could complete the three subcultures. Though some of the procedures could not be completed, final result could be concluded. Conclusion: In this preliminary study, 60 minute colagenase-1 digestion with intermittent shaking every 5 minutes and cell seeding around 50,000 or more, followed by subculture method without washing step gave the best result. (Med J Indones 2011; 20:15-9) Keywords: collagenase-1, primary culture, subculture, stromal-vascular fraction